More tell me why : answers to over 400 questions children ask most often - Leokum, Arkady; Koehler, Cynthia Iliff; Koehler, Alvin (New York : Hamlyn, 1967)
An encyclopedic collection of questions and answers about nature, man, inventions, and customs.
Includes index.
Keywords: Children's questions and answers -- Juvenile literature; Questions and answers